Naturally exposed populations differ in their T1 and T2 responses to the circumsporozoite protein of Plasmodium falciparum. - Reece, W; Plebanski, M; Akinwunmi, P; Gothard, P; Flanagan, K; Lee, E; Cortina-Borja, M; Hill, A; Pinder, M (2002)
T-cell responses directed against the circumsporozoite protein (CS) of Plasmodium falciparum can mediate protection against malaria. We determined the frequency of T cells reactive to different regions of the CS in the blood of donors naturally exposed to P. falciparum by examining T1 (gamma interferon [IFN-gamma] ELISPOT assay), T2 (interleukin 4 [IL-4] ELISPOT assay), and proliferative T-cell responses. The proliferative responses were weak, which confirmed previous observations. The responses to the CS in the IL-4 and IFN-gamma ELISPOT assays were also weak (<40 responding cells per 10(6) cells), much weaker than the response to the purified protein derivative of Mycobacterium tuberculosis in the same donors. Moreover, a response in one assay could not be used to predict a response in either of the other assays, suggesting that although these assays may measure different responding cells, all of the responses are weakly induced by natural exposure. Interestingly, the two different study populations used had significantly different T1 and T2 biases in their responses in the C terminus of the protein, suggesting that the extent of P. falciparum exposure can affect regulation of the immune system.